2021
DOI: 10.3390/ijerph18147620
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Problematic Internet Use in a Population of Spanish University Students

Abstract: (1) Background: To examine the prevalence, and associated factors of, problematic Internet use in a sample of Spanish university students. (2) Methods: Cross-sectional descriptive study of a convenience sample of 698 university students. Self-esteem, alcohol consumption, perceived social support, depression, anxiety, stress and problematic Internet use were evaluated using the Rosenberg, CAGE, DUKE-UNC-11, DASS-21 and Young’s Internet Addiction Test, respectively. (3) Results: Problematic internet use was repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 68 publications
(134 reference statements)
2
14
0
1
Order By: Relevance
“…were more likely to be addicted to the internet compared to students who lived at home. The results of Ramón-Arbués et al (39) also showed that the likelihood of problematic internet use was significantly related to the habitation status of college students. However, the results of this study are not consistent with those of Kivrak and Kivrak (83), who found that dormitory students suffer from internet addiction less than those staying at home.…”
Section: Housing During the Semestermentioning
confidence: 89%
See 3 more Smart Citations
“…were more likely to be addicted to the internet compared to students who lived at home. The results of Ramón-Arbués et al (39) also showed that the likelihood of problematic internet use was significantly related to the habitation status of college students. However, the results of this study are not consistent with those of Kivrak and Kivrak (83), who found that dormitory students suffer from internet addiction less than those staying at home.…”
Section: Housing During the Semestermentioning
confidence: 89%
“…In this case, respondents could select one of the following answers for each of the 10 items: never-−0, almost never-−1, sometimes-−2, fairly often-−3, very often-−4. The ranges of the total PSS-10 score indicated: low stress (0-13), moderate stress (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), and high stress (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Accordingly, the higher the total score, the more severe the psychological distress.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies were used to evaluate the association between IAD and smoking (20,37,40,45), suicidal behavior (20,37,39,43) and drinking (37,40,42,45,47,48). The heterogeneity was not significant (I 2 < 50%), and a fixed-effects model was applied.…”
Section: The Association Between Iad and Health Risk Behaviors Accord...mentioning
confidence: 99%